A novel regulation of PD-1 ligands on mesenchymal stromal cells through MMP-mediated proteolytic cleavage. (3rd March 2016) - Dezutter-Dambuyant, Colette; Durand, Isabelle; Alberti, Laurent; Bendriss-Vermare, Nathalie; Valladeau-Guilemond, Jenny; Duc, Adeline; Magron, Audrey; Morel, Anne-Pierre; Sisirak, Vanja; Rodriguez, Céline; Cox, David; Olive, Daniel; et al.
ABSTRACT: Whether fibroblasts regulate immune response is a crucial issue in the modulation of inflammatory responses. Herein, we demonstrate that foreskin fibroblasts (FFs) potently inhibit CD3 + T cell proliferation through a mechanism involving early apoptosis of activated T cells. Using blocking antibodies, we demonstrate that the inhibition of T cell proliferation occurs through cell-to-cell interactions implicating PD-1 receptor expressed on T cells and its ligands, PD-L1 and PD-L2, on fibroblasts. Dual PD-1 ligand neutralization is required to abrogate (i) binding of the PD-1-Fc fusion protein, (ii) early apoptosis of T cells, and (iii) inhibition of T cell proliferation. Of utmost importance, we provide the first evidence that PD-1 ligand expression is regulated through proteolytic cleavage by endogenous matrix metalloproteinases (MMPs) without transcriptional alteration during culture-time. Using (i) different purified enzymatic activities, (ii) MMP-specific inhibitors, and (iii) recombinant human MMP-9 and MMP-13, we demonstrated that in contrast to CD80/CD86, PD-L1 was selectively cleaved by MMP-13, while PD-L2 was sensitive to broader MMP activities. Their cleavage by exogenous MMP-9 and MMP-13 with loss of PD-1 binding domain resulted in the reversion of apoptotic signals on mitogen-activated CD3 + T cells. We suggest that MMP-dependent cleavage of PD-1 ligands on fibroblasts may limit their immunosuppressive capacity and thus contribute to the exacerbation of inflammation in tissues. In contrast, carcinoma-associated fibroblasts appear PD-1 ligand-depleted through MMP activity that may impair physical deletion of exhausted defective memory T cells through apoptosis and facilitate their regulatory functions. These observations should be considered when using the powerful PD-1/PD-L1 blocking immunotherapies.